SEISMIC BEHAVIOUR OF HIGH RISE BUILDING WITH SHEAR WALL - Santosh Anil Chothe1, PrafullaSubhashKamble2, Kuldip Pukale3. (International Journal of Innovations in Engineering Research and Technology, 2022)
Structural design of high-rise building under seismic loading isprimarily concerned with the provision of shear wall. The mostappropriatemethod for resisting lateral loads is shear wall systems. Conventional reinforced concrete shear wall and steel plate shear walls are used worldwide for resisting wind loadsand earthquake loads. Composite construction methods have accepted in the industry in which composite columns, beams and slabs are started in practice recently. Now researches on Composites hear wall had gained interest considering the advantages overreinforced concrete and steels hear walls.Providing better stiffness and ductility, reduction in dead load and thickness of the wall, better structural response, reducedcostand timeofconstruction etc. make composite shearwallan excellent system for earthquake resistant structures. Thispaperreviewstheinvestigationscarriedontheseismic behavior of shear wall in multistoreyuildingsusingariousapproaches.Researchersmainlyfocusedontheperformanceofdifferenttypesofcompositeshearwallincomparisonwithreinforcedandsteelplateshearwall.Experintalinvestigations give the better response of composite shear wallunder cyclic loading. The review reveals that though majorityof the literature is available related to the seismic behavior ofshear wall, a very little work is reported on composite shearwall in high rise buildings. From the available research papersit is understood that the composite action is the key behind thebetter performance of composite shear wall. This new systemshows satisfactory responseoveronventionashearwallsintermsofdisplacement,storeydrift,storeyshearandotherseismic parameters. It is understood that there are differentforms of composite shear wall, but adopting the best suitablemethod for different seismic zone has to be studied further.Thusitisnecessarytocarryoutmoreworkinordertoquantify the design criteria and structural performance of thecomposite shear wall under seismic effect. This emphasizes theimportance of the study of composite shear wall with referenceto Indian design criteria to promote the use of such successfulconstructiontechnology.